The Influence of Sharia Economic Politics on the Development of Sharia Financial Institutions in the Digital Era in Indonesia - Wahdatul Nadia Rawi; Latipah; Raudlatus Solihin (Penerbit Hellow Pustaka, 2025)
The development of Islamic financial institutions in Indonesia is growing rapidly, particularly with the advent of the digital era. Islamic economic politics plays a significant role in shaping policies and regulations that support the growth of this sector. This article examines how Islamic economic politics influences the development of Islamic financial institutions in Indonesia, focusing on the application of digital technology. Using a qualitative descriptive approach, this study identifies that government policies based on Islamic principles, coupled with technological innovation, are key factors in increasing access and efficiency of Islamic financial services. Based on data from the Financial Services Authority (OJK), the Islamic fintech sector in Indonesia has recorded growth of around 50% per year in recent years. Furthermore, Islamic fintech has also grown rapidly in recent years, offering various services such as digital payments, peer-to-peer (P2P) financing, and Islamic-based investments. The research method used in this study is a literature review.